The State of the Hungarian Pig Industry Following Accession to the European Union and its Impacts (2004-2013) - Vinkler, Belane (European Scientific Journal, ESJ, 2017)
The present paper aims to describe the period following Hungary’s accession to the European Union, its impacts on the country’s economy with special focus on the state of the national pig industry. After the EU accession, predictability within the industry became history; even the domestic prices of fodder are dependent on global market prices. A significant part of animal farmers do not own land and grow their fodder needs on rented plots or solve this problem by purchasing from the market. However, the constant fluctuations in the currency exchange rates and mercantile exchange speculations also influence prices and the income producing capability of animal farming. It is not surprising that because of the declining purchasing prices of pork and the unpredictability of fodder prices many farmers are considering giving up production. These days the change in external conditions is not only a constant phenomenon, but is showing a quickening trend posing a challenge to all countries. If they wish to stay successful in the long term, they have to take into account the internal and external changes alike, which directly or indirectly will have an impact the operation of the given country. Globalisation has become a fairly popular and often-used term to describe the processes inherent that make a significant effect on the labour market as well. It is important to assist in the stabilisation of the existing and operating pig farms so that we can utilize the potentials inherent in them. In this part (part I.) the pig industry and the situation changes of the pig population will be described until 2004-2013 period. In the next part (part II.) the structure of Hungarian pig industry and pork in the Hungarian pig sector until 2007-2013 period will be described.